2014
DOI: 10.1177/0954407013511072
|View full text |Cite
|
Sign up to set email alerts
|

Study on the twin-pilot-injection strategies for the reduction in the exhaust emissions in a low-compression-ratio engine

Abstract: An investigation of twin-pilot-injection strategies was performed in a low-compression-ratio engine in order to improve the combustion performance and to reduce the exhaust emissions. All tests were conducted on a modified four-cylinder test engine running on only one cylinder with a reduced compression ratio (15.3:1), and analyses of the combustion pressure, the heat release rate and the net work output in the cylinder were performed. At the same time, the reduction in the exhaust emissions such as carbon mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Previous researches have suggested that effects of injection rates and their shape on air-fuel mixing and combustion processes are significantly important to organising diesel combustion [12,13]. Suh [13] has conducted experiments on a high speed direct injection (HSDI) diesel engine for which compression ratio is 15.3 : 1 reduced from 17.8 : 1 by modification of combustion chamber shape to investigate the effects of the twin-pilot-injection strategies on combustion performance and exhaust emissions. The study shows lower NOx emissions (up to 45.7% were observed), whereas soot generation level was almost unaltered in the multiple-injection case.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have suggested that effects of injection rates and their shape on air-fuel mixing and combustion processes are significantly important to organising diesel combustion [12,13]. Suh [13] has conducted experiments on a high speed direct injection (HSDI) diesel engine for which compression ratio is 15.3 : 1 reduced from 17.8 : 1 by modification of combustion chamber shape to investigate the effects of the twin-pilot-injection strategies on combustion performance and exhaust emissions. The study shows lower NOx emissions (up to 45.7% were observed), whereas soot generation level was almost unaltered in the multiple-injection case.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the piston starts compressing the trapped air inside the cylinder while moving from BDC to top dead center (TDC). When the piston reaches a few crank angle degrees before TDC, the intake valve opens again (Figure 1(a)) and the hot compressed air inside the cylinder gets ejected at high velocities back into the intake air plenum (3). During this ejection process, the first portion of air coming out of the cylinder will be at the maximum temperature attained after compression.…”
Section: Conceptualization and Implementationmentioning
confidence: 99%
“…Since emission legislations are getting stringent, lower CRs are currently being preferred in diesel engines to achieve low NO x and soot emission levels. [1][2][3] Engine downsizing with high level of turbocharging is being used worldwide to meet the CO 2 emission regulation. So, it is necessary to reduce the CR in such highly boosted engines to limit the peak firing pressure, and hence there is an interest in automotive industry in exploring the benefits of low CR diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the fuel injection process significantly affect the combustion process in the cylinder, and consequently the engine power [3,4]. Every combustion engine, including CI engine is complicated as far as the adjustment is concerned.…”
Section: Introductionmentioning
confidence: 99%